2014
DOI: 10.3928/00485713-20141208-06
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase Inhibitors for Various Psychiatric Disorders and Conditions

Abstract: This article explores literature to determine if there are specific psychiatric disorders in which monoamine oxidase inhibition (MAOI) therapy proved effective. Evidence was considered adequate to deem MAOIs indicated for illnesses in which we found two or more randomized controlled trials (RCTs) demonstrating superiority of MAOI relative to a comparator. The comparator could be placebo or active drug. Equivalency studies in which two drugs are not found to differ were considered supportive of efficacy but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…MAOIs such as tranylcypromine and phenelzine have long been efficacious in treatment-resistant depression [44]. In adult studies, they have also been found to be efficacious in panic and social anxiety disorder [45].…”
Section: Monoamine Oxidase Inhibitors (Maois)mentioning
confidence: 99%
“…MAOIs such as tranylcypromine and phenelzine have long been efficacious in treatment-resistant depression [44]. In adult studies, they have also been found to be efficacious in panic and social anxiety disorder [45].…”
Section: Monoamine Oxidase Inhibitors (Maois)mentioning
confidence: 99%
“…Our results suggest potential therapeutic application of virodhamine for the treatment of Parkinson’s disease. Selective irreversible inhibitors of MAO-B have also shown promise for treatment of depression and Attention Deficit Hyperactivity Disorder (ADHD) [49, 50]. Selective MAO-B inhibition also leads to increase in endogenous β-phenylethylamine (PEA) levels in the brain [51].…”
Section: Discussionmentioning
confidence: 99%
“…34 Nine out of 12 RCTs have demonstrated benefit of irreversible MAOIs in panic and social anxiety disorder. 35 Phenelzine has also been shown to be as beneficial as tricyclic antidepressants in post-traumatic stress disorder (PTSD), 36,37 but not all trials have been consistent. 38…”
Section: Clinical Pharmacology and Safety Considerationsmentioning
confidence: 99%